Removal of Coin Cell Lithium Battery Lodged in the Pediatric Pharyngoesophageal Junction by Rigid Esophagoscopy; a Case Report - Ominato, Hisataka; Kumai, Takumi; Harabuchi, Yasuaki (Archives of Academic Emergency Medicine, 2022)
A coin cell lithium battery is a common foreign body that can become lodged in the pediatric pharyngoesophageal junction. Because the voltage of such batteries is relatively high, their rapid removal is necessary to avoid mucosal necrosis. Despite being the initial choice for removal, flexible endoscopy cannot remove such foreign bodies from the esophagus. Various removal methods, including rigid esophagoscopy, should be considered for removing lithium coin cell batteries. The transcervical approach is feasible for removing esophageal foreign bodies, but it carries the risk of complications such as esophageal stenosis. Here we report a case of lithium coin battery ingestion that was successfully removed using a rigid esophagoscope. A 2-year-old girl was referred to a local doctor with cough and general fatigue. Chest X-ray and flexible endoscopy revealed a coin cell lithium battery stuck in the pharyngoesophageal junction, but it could not be removed. The foreign body was removed using Nishihata forceps through a rigid esophagoscope under general anesthesia.